2023
DOI: 10.3390/polym15040956
|View full text |Cite
|
Sign up to set email alerts
|

Retentive Forces and Deformation of Fitting Surface in RPD Clasp Made of Polyether-Ether-Ketone (PEEK)

Abstract: Background: Polyetheretherketone (PEEK) has provided the option to fabricate RPDs with aesthetics unlike metal RPDs, but little attention has been paid to its suitability, especially towards the retentive forces and deformation of the clasp. This study aimed to examine the retentive forces and the fitting surface (inner surface) deformation of clasps made from PEEK and compare it with cobalt–chromium (Co-Cr) clasp. Methods: Forty-two circumferential clasps (14 Co-Cr and 28 PEEK) were fabricated and divided int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Similarly, exhaustive training is important to develop confidence among academicians so that they can smoothly operate the new technology. That will also lead to a developing attitude among academicians to decently use e-learning [ 87 , 88 , 89 , 90 , 91 , 92 ]. The study uses three external factors as predictors of perceived usefulness and perceived ease of use.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, exhaustive training is important to develop confidence among academicians so that they can smoothly operate the new technology. That will also lead to a developing attitude among academicians to decently use e-learning [ 87 , 88 , 89 , 90 , 91 , 92 ]. The study uses three external factors as predictors of perceived usefulness and perceived ease of use.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of studies have investigated all-ceramic restorations under the fracture fatigue resistance or until fractures occurred [ 32 , 37 , 38 ], yet none or limited studies investigated the connection between all-ceramic restorations and RPDs as reported in this study. The fracture test in this study was conducted by applying the fracture load to the saddle area which is connected to all-ceramic crowns by the occlusal rests.…”
Section: Discussionmentioning
confidence: 99%
“…Polyether ether ketone (PEEK) represents a biocompatible thermoplastic polymer with a hightemperature tolerance, characterized by an elastic modulus falling within the range of 3 to 4 GPa and a melting point proximate to 343˚C, in addition to exhibiting commendable mechanical properties (8)(9)(10) . Notably, PEEK has garnered attention as a substitute material for retentive caps in implant overdenture applications, offering advantages such as reduced wear, enhanced retention capabilities, heightened patient contentment, and the potential for decreased maintenance interventions (11,12) .…”
Section: Introductionmentioning
confidence: 99%